PP-044 Evaluation of the quantos® powder dosing system for capsule manufacturing in a hospital pharmacy. (14th February 2016) - Will, N; Vitt, M; Goerke, A; Loebering, M; Laukart, J; Baehr, M; Langebrake, C
Abstract : Background: The Quantos powder dosing system (Mettler Toledo, Germany) offers the filling of small amounts of powders and liquids into different containers. Although it is already used for handling hazardous substances and/or preclinical drug development, very little information exists for the routine manufacturing of capsules in a hospital pharmacy. Purpose: Evaluation of the accuracy and practicability of Quantos compared with the manual capsule filling (MAN) method in a hospital pharmacy. Material and methods: Different batches of hydrochlorothiazide and spironolactone capsules, at three dosage levels each, were produced using standard triturations. Quantification of the active ingredients was done by UV/Vis-spectroscopy using a validated method, and evaluation according to the standard examinations for capsules of the European Pharmacopoeia (PhEur 2.9.5/6 and 40) was performed. The time required for each production step was measured. Results: All batches passed the examinations for uniformity of mass and content (in relation to arithmetic mean) with a lower SD for Quantos versus MAN (1.91–3.35% vs 3.20–7.84%). Almost all batches contained about 90% of the declared dosage, although the content of the used triturations was almost 100%. As a consequence, PhEur 2.9.40, which additionally refers to the desired value, was passed more often by Quantos batches than MAN. In comparison with MAN, the Quantos system was slower. Conclusion: With both methods, capsules that are in accordance with the requirements of the PhEur can be produced. Although the Quantos system can fill the capsules more precisely and allows GMP conform documentation, the handling process for day to day capsule manufacturing can be improved. The recovery rate of about 90% might be due to incomplete emptying of the capsules before quantification. This finding also has major implications for the common practice of emptying capsules on the wards and needs further investigation. References and/or Acknowledgements: We thank Mettler Toledo for permitting the project by lending a Quantos powder dosing system. Conflict of interest.